ANALISIS KESULITAN DALAM MENYELESAIKAN MASALAH ABSTRAKSI MATEMATIS PADA POKOK BAHASAN FUNGSI - Nor Khasanah; Tri Atmojo Kusmayadi; Farida Nurhasanah (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
AbstractThe purpose of this study was to determine the types and factors that cause student difficulties in solving mathematical abstraction problems on the subject of functions. This research used a qualitative descriptive research type, with research subjects totaling 3 students of class VIII MTS Mada Nusantara Jepara in the academic year 2019/2020 who were taken by purposive sampling. The data collection techniques used were tests, interviews, and documentation. Data analysis used includes data reduction, data presentation, and drawing conclusions. The results of the research conclusions obtained are: 1) Types of difficulties in solving mathematical abstraction problems in the subject of functions, namely students having difficulty understanding the concept of functions, students having difficulty applying the right formula, students having difficulty connecting between concepts, and students having difficulty in carrying out operations. 2) Factors that cause students difficulty in solving mathematical abstraction problems on the subject of functions, namely students lack of practice in solving questions, students are confused about applying the right formula, students are less careful and in a hurry in solving questions, and students do not double-check their answers. Keywords: Causative Factor; Mathematical Abstraction; Student’s Difficulties